Bibliometric Analysis of the Evolution of Employee Stress from Burnout to Well-being - Tutik Winarsih; Fariz Fariz (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
Employee stress has gained significant attention in recent years due to its far-reaching impact on individual well-being and organizational outcomes. This study aims to identify current trends and patterns in employee stress research, explore influential journals that are driving innovation in organizational health studies, and explore new themes and topics related to workplace well-being in the face of the dynamics of the modern work environment. This study used bibliometric analysis to evaluate scientific publications related to employee stress contained in scientific articles published in leading journals between 1984 and 2023. The collection and analysis of relevant studies were conducted systematically by utilizing the Scopus database and using visualization tools, such as VOSviewer, and statistical software, namely Publish or Perish and Microsoft Excel. The research revealed key themes, such as “Resilience,” “Stress Management,” and “Workplace Wellbeing,” that indicate increasing attention to understanding and addressing employee stress. The analysis also identified influential academic works and leading institutions that contributed to the development of this research. This study advances employee stress research by mapping trends, recognizing key research areas, and identifying seminal works.